The Correlation Between Concentration PM 2.5 Of The Possibility Of Acute Respiratory Infections Diseases - Hemas, Caroline Kartika; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
ARI Acute Respiratory Infections or a respiratory illness that can last up to 14 days. ARI has become one of the major causes of morbidity and mortality in children in developed and developing countries, especially for children younger than 5 years. A respiratory infection causes approximately 20% of the deaths of children aged under 5 years. Various factors cause ARI. One of the causes of respiratory disease is small particulate size. This study carried out particulate matter measurements indoor and questionnaires to determine the community's habits conducted in 30 houses randomly in settlements around the overpass Pasopati Bandung. Based on RTBL (Layout Plan of Building and Environment), this study was carried out, especially in RW 4, 10, 11, 15Taman Sari Village. Measurements of PM2.5 were carried out continuously for Â±24 hours at one location in the house. Possible sources of particulate matter come from the Pasopati flyovers, soccer fields located beneath the Pasopati flyovers, and community activities daily, such as smoking, cooking, and burning trash.